Dosis de gallinaza y su influencia en las características agronómicas de Brassica olerácea L. var. capitata, Fuyotokio, en Zungarococha-Loreto.2022 - Torres Tapullima, Jerry Hildemaro (2022)
The experimentation was forged in the lands of the Faculty of Agronomy, of the UNAP, located near the town of Zungarococha-Iquitos, having had as its primary objective the evaluation of the influence of the doses of chicken, in the agronomic characteristics and yield of Brassica olerácea L, var.capitata, Fuyotokio, The experimental sketch was that of Completely Random Blocks, whose results were analyzed and discussed through Analysis of Variance, and Tukey's comparison test. With the results obtained, the following conclusions were reached: The best results were achieved by T4 (60 t of chicken / ha), being statistically superior in the variables of plant height, plant diameter, number of leaves / plant, root length, root weight, head diameter, total plant weight, head weight and head weight / ha; likewise, the yield was 30.74 t of heads/ha with an economic income of S/.79,550.00.